IMPLEMENTATION OF 2013 CURRICULUM CHALLENGES AT NURUL JADID VOCATIONAL SCHOOL - Aini, Intan Nur; Khaer, Abu; Lestari, Yusi Dwi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Curriculum change is an unavoidable necessity, where curriculum development must be implemented in response to the demands of the times. However, in practice, the transition from the 2006 Curriculum (KTSP) to the 2013 Curriculum faces various challenges. This study aims to analyze the issues encountered in the implementation of the 2013 Curriculum by schools, teachers, and students. The method used is qualitative research, with data sources including the principal, vice principal, teachers, educational staff, and students of SMK Nurul Jadid. Data collection techniques include document reviews, participatory observations, and in-depth interviews. Data analysis employs an interactive model, and the validity of the data is tested through triangulation. The results indicate several challenges in the implementation of the 2013 Curriculum, such as frequent changes in regulations and repeated revisions, uneven training for teachers, limitations in facilities and infrastructure, as well as insufficient textbooks for teachers and students. Additionally, there are issues related to the transformation of scientific culture, school literacy movements, and suboptimal internal supervision.